Investigating the Properties and Cytotoxicity of Cisplatin-Loaded Nano-Polybutylcyanoacrylate on Breast Cancer Cells - Gorgzadeh, Amirsasan; Hheidari, Ali; Ghanbarikondori, Parizad; Arastonejad, Mahshid; Ghasemi Goki, Tayebeh; Aria, Mehrad; Allahyartorkaman, Ahmadreza; Moazzam, Farimah; Jabbari Velisdeh, Zeinab; Saberian, Elham; et al. (Asian Pacific Journal of Cancer Biology, 2023)
Background: This study aimed to develop a novel drug formulation using polybutylcyanoacrylate (PBCA) nanoparticles to deliver cisplatin, a commonly used chemotherapeutic agent for breast cancer treatment. Materials and Methods: PBCA nanoparticles were synthesized using a mini-emulsion polymerization method, and the resulting NPs were comprehensively characterized for their physical properties, such as size, size distribution, zeta potential, drug loading, and encapsulation efficiency. In addition, the cytotoxicity of the NPs was assessed, along with their ability to release the entrapped drugs over time. Results: The results showed that the PBCA nanoparticles had a mean size of 457 ± 7.4 nm, a size distribution of 0.253±0.011 and a negative zeta potential of -12.3 ± 1.3 mV. The drug encapsulation efficiency and loading capacity of cisplatin-PBCA were found to be 45.6 ± 2.7% and 3.5 ±0.8%, respectively; The release of the drug from the PBCA was estimated to be approximately 12.2±1.1% after 45 hours. The cytotoxic effects of the nanoparticle formulation were significantly enhanced compared to the free drug. The cytotoxicity of cisplatin-PBCA was evaluated in the T-47D breast cancer cell line, showing promising results as a potential drug formulation for breast cancer therapy. Conclusions: These findings suggest that cisplatin-PBCA may offer advantages over traditional cisplatin formulations, potentially improving the efficacy and reducing the toxicity of breast cancer treatment.